HUBUNGAN PEER ATTACHMENT DENGAN SELF REGULATED LEARNING PADA SISWA BOARDING SCHOOL - Mahmudi, Faisal; Mayangsari, Marina Dwi; Rachmah, Dwi Nur (Jurnal Ecopsy, 2015)
Penelitian ini bertujuan untuk mengetahui hubungan peer attachment dengan self regulated learning pada siswa Boarding School. Subjek penelitian yaitu siswa/siswi kelas XI SMAN Banua Kalimantan Selatan Bilingual Boarding School berjumlah 62 siswa. Metode penelitian yang digunakan adalah penelitian kuantitatif, dengan menggunakan teknik purposive random sampling. Instrument yang digunakan adalah skala peer attachment dan skala self regulated Learning. Hasil penelitian menunjukkan ada hubungan yang signifikan antara peer attachment dengan self regulated learning pada Siswa SMAN Banua Kalimantan Selatan Bilingual Boarding School. Sumbangan efektif yang diberikan variabel peer attachment terhadap self regulated learning adalah sebesar 9,8%. Semakin tinggi peer attachment maka akan semakin tinggi self regulated learning pada siswa Boarding School. Kata Kunci: Peer Attachment, Self Regulated Learning, Boarding School The purpose of this study was to find out the relationship between peer attachment and self-regulated learning in students of SMA Boarding School. The subjects were 62 students of class XI at SMAN BANUA Bilingual Boarding School South Kalimantan. A quantitative study method with purposive random sampling technique was used in this study. The instruments were Peer Attachment Scale and Self-Regulated Learning Scale. The result indicating that there was a significant relationship between peer attachment and self-regulated learning in students of SMAN BANUA Bilingual Boarding School South Kalimantan. The effective contribution of peer attachment to self-regulated learning variable was 9.8%. so that the higher the peer attachment, the higher the self-regulated learning in students of SMA Boarding School. Keywords: Peer Attachment, Self Regulated Learning, Boarding School